Some aspects of web-courses in mathematics based on PC screen recorded video lectures - Lukkassen, Dag; Persson, Lars-Erik; Sierpinska, Anna (NOMAD Nordic Studies in Mathematics Education, 2007)
In this paper we will describe and discuss two graduate level web-based mathematics courses based on PC screen recorded video lectures. These courses have been developed by the first author of this paper and followed by master’s students at the Narvik University College since 2001. Comparison to other available courses is made. We argue that the technical solutions, our personal positive experiences and didactical ideas (e.g. concerning the physical presence of students and teachers in addition to instruction by video) in relation to our concept constitute an interesting field for mathematical education research.